2021
DOI: 10.17485/ijst/v14i8.190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of comfort and thermal properties of stretch denim fabric by applying different softeners

Abstract: Denim plays a vital role in the fashion industry. But today's fashion not only concern about its aesthetic property but also its comfortability. Objective: This study was aimed to explore the effect of different softeners on the comfort and thermal feeling properties of stretch denim fabric. Method/analysis: For the understanding of comfort, feeling, and thermal properties of stretch denim fabric in conjunction with enzyme wash and stone enzyme wash; different softeners like cationic, anionic, nonionic, micro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…It was found that non-ionic and anionic softeners applied fabrics had low thermal conductivity values. 10 Şen et al investigated the fastness and dimensional stability of regenerated cellulose fibers such as Naia™, Tencel, and Ecocell knitted fabrics. It was found that regenerated cellulose fibers could be an alternative to cotton and could be used in clothing because of their comfort properties 6 The effects of using elastane, T400 elastane, and wool elastane yarns in denim structures have been investigated in a previous study.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that non-ionic and anionic softeners applied fabrics had low thermal conductivity values. 10 Şen et al investigated the fastness and dimensional stability of regenerated cellulose fibers such as Naia™, Tencel, and Ecocell knitted fabrics. It was found that regenerated cellulose fibers could be an alternative to cotton and could be used in clothing because of their comfort properties 6 The effects of using elastane, T400 elastane, and wool elastane yarns in denim structures have been investigated in a previous study.…”
Section: Introductionmentioning
confidence: 99%
“…Adding elastane to denim fabrics increases the thermal resistance of samples and gives a warm feeling and increases the water vapor resistance of fabric specimens [13]. Hosen et al [14] investigated the effect of different softeners on the thermal and comfort ADYU Mühendislik Bilimleri Dergisi 18 (2022) 548-561 features of stretch denim fabrics. Different types of enzymes and softeners were applied to %98 cotton and %2 elastane including denim fabric.…”
Section: Introductionmentioning
confidence: 99%
“…It goes without saying that, no other fabric in this fashion world has been granted such widespread acceptance of denim among textile products [1][2][3]. Denim fashion is now widely used by individuals of all ages, classes and genders [4].…”
Section: Introductionmentioning
confidence: 99%